PENGEMBANGAN KAWASAN KONSERVASI LAUT DALAM KAITANNYA DENGAN PERLINDUNGAN IKAN PURBA COELACANTH DI PERAIRAN TAMAN NASIONAL BUNAKEN (SULAWESI UTARA) - , christiansen samadi, SH, Endang Purwaningsih, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purposes of this research are: (1) to acknowledge the strategy of marine protected area development in building the sustainable development of marine resources, and (2) to find out the efforts that have been made in protecting the Coelacanth old fish, on the illegal catch of scarce animal in North Sulawesi. This research about the development of marine protected area in relation to Coelacanth old fish protection is using empirical normative method. Normative legal research includes documents, legal articles, positive law or legal literature which is secondary data. The relevance of this legal substance is based on certain criteria such as primary legal substance, secondary legal substance and tertiary. Empirical research is a discovery of actual problem on the development of marine protected area in Taman Nasional Bunaken and the protection efforts towards the Coelacanth old fish in North Sulawesi province. The result of this research shows the common problems related to marine protected area management are the lack of society involvement, unsupported of law enforcement, unstable management of marine protected area and lack of alternative profession of the local community. The other problem related to the protection of Coelacanth old fish is the effect of reward problems given to fisherman for catching Coelacanth old fish. The implementation of the development of marine protected area in Taman Nasional Bunaken and legal protection for Coelacanth old fish is based on sustainable protection zone, recovery of damage coral triangle through coral rehabilitation and mangrove management. Protection on Coelacanth old fish is rules on CITES, CBD, UNCLOS 1982, other existed acts and form new act in realtion to Coelacanth old fish protection.